IN FIRE WE STRONG: THE ROLE OF RESILIENCE IN EXAMINING HELP ATTITUDE TO ADOLESCENCE POST TRAUMATIC GROWTH - Naurah Nadzifah; Devie Yundianto; Muhammad Khatami (Universitas Gunadarma, 2022)
The fire in Tambora, West Jakarta, is a man-made disaster. It occasionally happened because of its type of disaster. The uniqueness of this study is to see how the attitude of Adolescence to help each other during a disaster can affect post-traumatic growth (PTG), which is moderated by resilience. The research method used is a quantitative method with moderated regression analysis technique. The results show that PTG will grow even more when teenagers have a helpful attitude and are supported by good resilience.